(untitled) (Ex Chordis, 2024)
This article approaches the compositional process of the piece The Shimmer Beneath: A Scattering Attempt, for cello duo with amplification (2019). This research is part of my doctoral thesis The Composition of Timbre: A Multidimensional Approach (University of Leeds, 2021), in which I approach the timbral complexity from the possible correlations between its semantics and physicality. Here I focus on the study of luminance as one of the semantic dimensions of timbre, presenting different perspectives from psychoacoustics to contemporary repertoire for bowed strings. The compositional methodology includes the development of a scale for measuring the amount and intensity of light perceived in a series of cello techniques and their corresponding timbral qualitative descriptors. These technical explorations are spectrally analyzed to identify their timbral content and structure. The cello techniques are the ‘device’ for the timbral formation and development of the piece, according to a conceptual reference related to the experience of light.